“THE AUSTRALIAN” MEDIA’S PERSPECTIVE TOWARDS PRABOWO SUBIANTO’S VICTORY CLAIM: A CRITICAL DISCOURSE ANALYSIS - Rahelita Luki Yuvitasari (LITERA KULTURA : Journal of Literary and Cultural Studies, 2020)
Mass media has been a massive influence on showing the perspective towards a certain issue to the people. Furthermore, media as a part of discourse has a huge part of framing the certain issue and show the neutralism of the media towards what is conveyed in the news. This study aims to reveal the perspective that The Australian media was trying to portray upon the political condition in Indonesia under the situation of recent presidential election. This study uses socio-political theory of critical discourse analysis to reveal the neutralism or which side that the media is supporting to. It is found using Critical Discourse Analysis that The Australian media indicated to portray the foregrounding towards Prabowo and benefits the back-grounded side which is the incumbent, Joko Widodo. Key words: media, critical discourse analysis, the Australian media, politics.